2018
DOI: 10.1016/j.exer.2018.07.024
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the elastic fibre system within the mouse and human cornea

Abstract: The cornea relies on its organised extracellular matrix for maintaining transparency and biomechanical strength. Studies have identified an elastic fibre system within the human posterior cornea, thought to allow for slight deformations in response to internal pressure fluctuations within the eye. However, the type of elastic fibres that exist within the cornea and their roles remain elusive. The aim of this study was to compare the distribution and organisation of the elastic fibres within the posterior perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…This technique is believed to be specific for elastic fiber enhancement, and this was confirmed in our previous publication using antibody staining specific to elastin and fibrillin-1. 32 Our results showed that elastic fibers are present from week 12 of fetal development and are confined to the posterior corneal stroma.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…This technique is believed to be specific for elastic fiber enhancement, and this was confirmed in our previous publication using antibody staining specific to elastin and fibrillin-1. 32 Our results showed that elastic fibers are present from week 12 of fetal development and are confined to the posterior corneal stroma.…”
Section: Discussionsupporting
confidence: 53%
“…The tannic acid–uranyl acetate method has been previously described in numerous studies to enhance the contrast for elastic fibers within the cornea. 18 - 20 , 31 , 32 The elastic fibers were imaged as bundles of fibrillin-rich microfibrils, with some fibers containing an elastin core, characteristic of true elastic fibers, as described by previous studies. 18 The elastic fibers were initially identified from week 12 of corneal development as small and round bundles of microfibrils concentrated within the posterior peripheral region of the cornea.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we observed reduced expression of collagen-VI, which is constitutively expressed in the corneal stroma 90 . Reduction in COLVI could promote CNV by altering the corneal biomechanics.…”
Section: Discussionmentioning
confidence: 65%
“…As is well known, the human cornea is rich in extracellular matrix (ECM), which maintains corneal transparency and biomechanical strength [12]. Through medical biochemistry techniques-such as immunostaining technology-and proteomics, different abnormalities related to varying risk genes in the expression of ECM components were identi ed in KC patients [13].…”
Section: Genementioning
confidence: 99%